Bias at the intersection of race and gender: Evidence from preschool‐aged children. Issue 3 (23rd January 2019) - Perszyk, Danielle R.; Lei, Ryan F.; Bodenhausen, Galen V.; Richeson, Jennifer A.; Waxman, Sandra R.
Abstract: There is ample evidence of racial and gender bias in young children, but thus far this evidence comes almost exclusively from children's responses to a single social category (either race or gender). Yet we are each simultaneously members of many social categories (including our race and gender). Among adults, racial and gender biases intersect: negative racial biases are expressed more strongly against males than females. Here, we consider the developmental origin of bias at the intersection of race and gender. Relying on both implicit and explicit measures, we assessed 4‐year‐old children's responses to target images of children who varied systematically in both race (Black and White) and gender (male and female). Children revealed a strong and consistent pro‐White bias. This racial bias was expressed more strongly for males than females: children's responses to Black boys were less positive than to Black girls, White boys or White girls. This outcome, which constitutes the earliest evidence of bias at the intersection of race and gender, underscores the importance of addressing bias in the first years of life. Abstract : Children revealed a strong and consistent pro‐White bias. This racial bias was expressed more strongly for males than females: children's responses to Black boys were less positive than to Black girls, White boys or White girls. This outcome constitutes the earliest evidence of bias at the intersection of race and gender.